Extraction of Silica (SiO2) from Rare-Earth Metal Zircon (ZrSiO4) as Lithium-Ion Battery Anode Material - Putri Lestari; Rhiska Aria Berliani; Erlangga Aria Pratama; Ridwan Assabila Al-Jannata; Desy Vita Pratiwi; Hendri Widiyandari (Jurnal Kimia Sains dan Aplikasi, 2023)
Zircon is a rare metal natural mineral composed of zirconia and silica. The silica content in zircon can be used as anode material for lithium-ion batteries because of the low cost and high theoretical capacity. Silica is obtained from the extraction process of zircon with 5M NaOH solution with aging time variation to determine the silica surface area. The SiO2/C composite was obtained from the solid state reaction process of a mixture of silica and graphite. The silica results obtained were tested for characteristics using X-ray diffraction (XRD), Surface area analyzer (SAA), and Scanning electron microscopy/Energy dispersive x-ray (SEM/EDX). Test the battery performance to find the number of cycles, capacity, voltage, and battery current using Cyclic voltammetry (CV) and Continuous discharging current (CDC) tests. The highest silica yield and optimal surface area were obtained at 24 hours aging time variation of 8,721 m2/g with percentages of O 36.48% and Si 18.04%, and battery performance test with the highest capacity of 222.7 mAh/g on silica aging time variation 18 hours.